TRANSFORMASI EKONOMI RUMAH TANGGA PEREMPUAN PEDESAAN MELALUI PEMANFAATAN FINTECH SYARIAH - Kasmiati, Kasmiati (Fakultas Ekonomi Bisnis Islam, 2025)
This study aims to analyze how the utilization of Islamic fintech contributes to the economic transformation of rural women’s households. The research is grounded in the reality that rural women often face limited access to formal financial services due to geographical barriers, low financial literacy, and minimal asset ownership, making Islamic fintech a potentially inclusive solution aligned with their religious values. This study employs a qualitative approach with a case study design, involving women who have used Islamic fintech for at least one year, supported by additional informants, and utilizing in-depth interviews, observations, and documentation techniques. The findings reveal that Islamic fintech provides easier and faster access to financing through digital processes without complex administrative requirements, enabling women to obtain capital for developing micro-enterprises. Furthermore, digital features such as transaction recording, payment reminders, and budgeting tools encourage positive changes in household financial management and enhance women's financial literacy. The study also identifies socio-economic impacts, including increased autonomy, roles, and contributions of women in household economic decision-making, despite existing challenges related to digital literacy and limited internet infrastructure. Overall, the results highlight that Islamic fintech serves as a strategic instrument capable of strengthening the economic capacity of rural women and supporting the sustainable transformation of household economies.